2010
DOI: 10.3109/10715761003610752
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypothermia suppressed excessive generation of superoxide anion radical and inflammatory reactions in blood and liver in heatstroke: Laboratory study in rats

Abstract: The study was performed to demonstrate superoxide radical (O(2).-) generation, systemic inflammation and liver injury caused by heatstroke and to reveal suppressive effects of moderate hypothermia. Heatstroke was defined as achieving pharyngeal temperature of 40 degrees C with arterial pressure reduction. Heatstroke rats were divided to four groups by the temperature after the onset; 40 degrees C, 37 degrees C, 32 degrees C and sham-treated with 37 degrees C. O(2).- current was measured continuously in the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Subnormothermic temperatures have been found to have strong anti‐inflammatory properties similar to the additives described above. In rodent and porcine models, it has been demonstrated that temperatures of 33°C‐34°C reduce Kupffer cell activation and suppress release of IL1, IL6, and TNF‐α . In preliminary studies, we found that the combination of different strategies is most effective to block the activation of proinflammatory pathways during ex vivo perfusion.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Subnormothermic temperatures have been found to have strong anti‐inflammatory properties similar to the additives described above. In rodent and porcine models, it has been demonstrated that temperatures of 33°C‐34°C reduce Kupffer cell activation and suppress release of IL1, IL6, and TNF‐α . In preliminary studies, we found that the combination of different strategies is most effective to block the activation of proinflammatory pathways during ex vivo perfusion.…”
Section: Discussionmentioning
confidence: 89%
“…In rodent and porcine models, it has been demonstrated that temperatures of 338C-348C reduce Kupffer cell activation and suppress release of IL1, IL6, and TNF-a. (5)(6)(7)(8) In preliminary studies, we found that the combination of different strategies is most effective to block the activation of proinflammatory pathways during ex vivo perfusion. Therefore, the strategy of our perfusion setup was to combine the benefits of perfusing livers at close to normal temperatures of 338C with the benefits of adding several anti-inflammatory strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the mass screening, traditional studies on the specific target genes have been steadily undertaken. These studies usually focus on genes related with well-known pathways such as cell death or survival [4, 39, 48-50], inflammation [51-57], and free radicals [58-60]. Although inflammation may be a sequel of brain injury as well as infection, injury-related inflammation is a focus of the current reivew.…”
Section: Pharmacological Targets For Drug Developmentmentioning
confidence: 99%